Subsurface imaging of samples with SAM - LITNIEWSKI, J. (Archives of Acoustics, 1994)
The paper presents unique abilities of the acoustic microscope to penetrate and visualize an interior of materials which are opaque to the light. The construction of an acoustic lens optimized for subsurface imaging is described. The lens enables to achieve resolution of approximately 100 μm at 100 MHz frequency when visualize an interior of aluminum sample. Images of the back side of a coin and of a die attach bond of integrated circuit with ceramic package are presented.